Introduction of Traditional Games as a Way to Increase Physical Activity to Prevent Coronary Heart Disease at Al-Jihad Islamic Boarding School - Danny Irawan; Hotimah Masdan Salim; Mia Puspitasari; Akbar Reza Muhammad; Dian Dakwatul Choiriya (Indonesia Berdaya, 2026)
Coronary Heart Disease (CHD) is often caused by an unhealthy lifestyle, including lack of physical activity. Many Islamic boarding school students are unaware of the importance of physical activity to prevent coronary heart disease. Traditional Indonesian games, which are rich in cultural values, can be an effective means to increase physical activity while reintroducing cultural heritage to the younger generation. This activity aims to determine the effect of providing knowledge about the introduction of traditional games as an increase in physical activity in preventing coronary heart disease. The activity was carried out by providing knowledge. The level of change in knowledge was obtained by differentiating the results of the pre-test and post-test. Data calculations using statistical calculations were then carried out with a non-parametric analysis of the Wilcoxon signed-rank test. The activity showed an increase in students' knowledge about coronary heart disease and its prevention (p<0.05) and an increase in students' knowledge about the use of traditional games in increasing physical activity (p<0.05). Providing health education to students at the Al Jihad Islamic Boarding School in Surabaya was able to increase students' knowledge of the benefits of traditional games as an increase in physical activity to prevent coronary heart disease.